(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of the practice of pharmaceutical services in a hospital of the Unified Health System (Sistema Único de Saúde - SUS) and describe the development outcomes of the technical and clinical activities performed. Method: A descriptive study, with an experience report, was carried out at the Hospital Estadual de Ribeirão Preto, in the year 2021. The institution is a medium-sized hospital complex that provides health care (hospital and outpatient) to Ribeirão Preto, State of São Paulo, and 25 other neighboring municipalities. Pharmaceutical services were performed by nine pharmacists and a pharmacy assistant, as well as being characterized by operational and clinical practices. The report of the sector’s daily life was then detailed as a successful experience of the SUS. Results: Pharmaceutical services were structured through an institutional policy of safety in the use of medicines, which standardized the selection and distribution of medicines, taking into account good practices and the adoption of methods to avoid errors and adverse events. In addition, clinical services related to pharmaceutical care included medication reconciliation, pharmacotherapy review and pharmacotherapeutic follow-up, which were guided by evidence-based health practice. A 91.3% rate of acceptance by the health team to the actions of pharmaceutical services provided validation of the method used and the more than 750 interventions (technical and clinical) carried out supported the success of the experience. Conclusion: This study exposed a real-life experience related to the development of pharmaceutical services in a SUS hospital institution and it can support the structuring of these practices in other similar units.